2005
DOI: 10.1111/j.1740-8709.2005.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Household dietary strategies to enhance the content and bioavailability of iron, zinc and calcium of selected rice‐ and maize‐based Philippine complementary foods

Abstract: Philippine complementary foods are predominantly plant-based, with a low content of readily available iron, zinc, and calcium, and a relatively high amount of phytate, a potent inhibitor of mineral absorption. Some of the phytate is water soluble, and hence can be removed by soaking. In this study we have compared the iron, zinc, and calcium content, and estimated iron and zinc bioavailability of rice- and maize-based Filipino complementary foods prepared with and without soaking and/or enrichment with chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…This result could be related with the fact that as other researchers had previously concluded, the food treatment significantly increased the Ca availability as a consequence of the diminishment of phytic acid content, polyphenols and trypsin inhibitor activity [13,14,26]. Other researchers [25] pointed out that industrially processed legumes had higher Ca dialysabilites.…”
Section: Total and Dialysable Ca Fractions And Corresponding Ca Dialymentioning
confidence: 49%
See 2 more Smart Citations
“…This result could be related with the fact that as other researchers had previously concluded, the food treatment significantly increased the Ca availability as a consequence of the diminishment of phytic acid content, polyphenols and trypsin inhibitor activity [13,14,26]. Other researchers [25] pointed out that industrially processed legumes had higher Ca dialysabilites.…”
Section: Total and Dialysable Ca Fractions And Corresponding Ca Dialymentioning
confidence: 49%
“…Additionally, the influence that other nutrients also present in meals might have on dialysable mineral fractions was also done [6]. Besides, the Mg and Ca absorption from foods depends on the elements and their transformation during food processing and food digestion [5,13,14,23,[25][26][27][28][29]. Therefore, both factors were also studied in these duplicate ready-to-eat meals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, several researchers have reported the negative influence of the phytic acid content of food and meals on iron dialyzability (1,(7)(8)12,18,20,23,29,(30)(31)(32).…”
Section: Resultsmentioning
confidence: 97%
“…(1,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Singh et al (24) reported that, in the presence of abundant and varied food supplies, the health consequences of lower iron bioavailability are unclear and require further investigation.…”
mentioning
confidence: 96%